Empowering Fish Cultivator Groups in Water-Minimum Areas by Cultivating Ospronemous gouramy Fish in Probiotic Media Tarpaulin Ponds in Asahduren Village, Jembrana Regency, Bali Province - I Wayan Arya; I Gusti Gurah Sugiana; I Dewa Nyoman Sadguna; I Gede Sudiarta; N. Pangki Pangemanan (Jurnal Pengabdian Masyarakat Bestari, 2023)
This National Community Partnership Program (PKM) is a collaboration between Warmadewa University, Denpasar and Sam Ratulangi University, Manado with partner fish cultivator group (Pokdakan) "Mina Dewata" in Asahduren Village, Pekutatan District, Jembrana, Bali. This PKM aims to optimize the use of water and land resources while increasing Pokdakan productivity by cultivating gourami fish in tarpaulin ponds with probiotic media. The cultivation container is in the form of a tarpaulin pond with water media treated with probiotics, so that it saves water and the water quality remains healthy for the growth of gourami fish. The program is implemented using the applied study method, including: 1) Cultivating gourami fish in tarpaulin ponds with probiotic media; and 2) Increasing the capacity and competence of Pokdakan. In this initial stage, the group has succeeded in creating 4 cultivation ponds out of the 12 planned ponds.